Validation of DOR Bt 127 SC against capitulum borer, Helicoverpa armigera and coccinellid predators in Sunflower: Validation of DOR Bt 127 SC against capitulum borer, Helicoverpa armigera and coccinellid predators in Sunflower - K M SRINIVAS REDDY; C P MANJULA; K S SOMASHEKHAR; S D NEHRU; M S UMA (Journal of Oilseeds Research, 2023)
DOR Bt 127 SC was evaluated against capitulum borer Helicoverpa armigera and coccinellid beetles in sunflower crop during Kharif 2020 at farmers field, Myakalurahalli, Hiriyur Tq, Chitradurga dt., Karnataka. DOR Bt 127 SC was compared with Chlorantraniliprole 18.5 SC and farmer’s practice. Chlorantraniliprole 18.5 Sc treated plot registered significantly lowest population (0.23) of H. armigera and was on par with Bt 127 Sc (0.40) during 10 days after spray. Farmers’ practice registered significantly highest population (1.33) of H. armigera.